Chiral conglomerates observed for a binary mixture of a nematic liquid crystal trimer and 6OCB. Issue 45 (23rd September 2015) - Yoshizawa, Atsushi; Kato, Yusuke; Sasaki, Haruna; Takanishi, Yoichi; Yamamoto, Jun
Abstract : Interactions between a phenylpyrimidine unit of trimer1 and a cyanobiphenyl unit of6OCB can produce a twist conformation of the central biphenyl of the trimer, which induces chiral segregation and layer deformation to drive the chiral conglomerates. Abstract : Dark conglomerates of domains with opposite handedness, which are designated as dark conglomerate phases (DC phases), have attracted much attention. After designing an achiral liquid crystal trimer, 4, 4′-bis{7-[4-(5-octyloxypyrimidin-2-yl)phenyloxy]heptyloxy}biphenyl (1 ), which exhibits only a nematic phase, we prepared binary mixtures with some typical rod-like nematic liquid crystals, i.e., 4′-hexyloxy-4-cyanobiphenyl (6OCB ), 2-(4-hexyloxyphenyl)-5-pentyloxypyrimidine (PPY ), or 4-methyloxyphenyl 4-hexyloxycyclohexanecarboxylate (PCA ), and investigated their phase transition behaviour. The binary mixtures containing 55–90 mol% of6OCB were found to exhibit a nematic phase and a DC phase of chiral domains with opposite handedness. However, neitherPPY norPCA induced such a chiral conglomerate phase in the mixture with trimer1 . We discuss how core–core interactions contribute to produce such a chiral conglomerate phase.